"Operation Eagle Eye": Border Citizenship and Cross-border Voting in Ghana's Fourth Republic. Issue 1 (2nd January 2023) - Adotey, Edem
ABSTRACT: This article examines the role of elections in bordering through disputes over cross-border voting since Ghana returned to multi-party democracy in 1992. It uses case studies from some communities that border Togo in the Volta Region of Ghana which is the epicenter of alleged cross-border voting. In these communities, "border citizenship" is expressed through the deployment of ritual space, social and political relations which is across national borders. But this begs the question whether border citizens view voting as a right or not, or more specifically, contest the border by participating in elections on either side of the border. This article argues that border citizens are not only involved in contesting the border; one can assume to have a border citizenship and still respect the border in elections by refusing the act of cross-border voting. This study not only contributes to border studies by highlighting the importance of electoral politics in the bordering process but it also brings to light the complexities of cross-border voting, since it shows that border residents in the Ghana-Togo borderland communities do not all perceive cross-border voting positively.